Effect of treatment with sunflower oil and in combination with pomegranate and plum sauce on the chemical, microbiological and sensory properties of marinated Carp fillets (Cyprinus carpio) - Fatih Korkmaz; Ali Arslan; Alper Baran (Ciência Rural, 2021)
ABSTRACT: The effect of sunflower oil (SO), sunflower oil-pomegranate sauce (PS1) and sunflower oil-plum sauce (PS2) on shelf life of marinated carp fillets was investigated in terms of sensory evaluation, chemical (peroxide value (POV), thiobarbituric acid (TBA), free fatty acids (FFA), total volatile basic nitrogen (TVB-N) and pH), and microbiological properties (Total viable count (TVC), Escherichia coli, Total coliform, Staphylococci/Micrococci, Salmonella spp.) during 30 days of storage. Proximate composition, which includes total crude protein%, fat%, moisture% and ash% of fresh carp fillets before marination process was analyzed and found 18.69±0.86, 4.08±0.19, 74.33±0.63 and 2.17±0.45, respectively. Sensory evaluation analysis showed that total appearance, odor-taste and texture scores decreased during storage. TVB-N significantly increased in all group after 1 month of storage (P<0.05). At the end of storage, the lowest TBA value (1.38 mg MA/kg carp fillet) was determined in the PS1 group. During storage, the highest POV value was observed in the control group (8.49 mEq O2/kg) compared to other groups. Initial TVC of 1.5 log CFU/g, 1.7 log CFU/g and 1.8 log CFU/g increased to 3.7 log CFU/g, 2.9 log CFU/g and 3.2 log CFU/g in SO, PS1 and PS2 groups, respectively. Results showed that the shelf life of marinated carp fillets treated with sunflower oil and in combination with pomegranate and plum sauce was more than 1 month.